Avaliação do processo de reabilitação de idosos com déficit de equilíbrio por meio da plataforma Wii Balance BoardTM - Batista, Juliana Secchi (2012)
The aging process creates functional and structural changes in the body. Among these changes, the systems responsible for balance control are also affected, especially in women. This study aimed to conduct an assessment and a physical therapy intervention in the elderly with balance deficits through the Berg Scale and Balance Board Wii platform. The research is a longitudinal quasi-experimental intervention. The sample consisted of 38 elderly women who had a deficit balance. The instruments used for data collection were a questionnaire to identify, assess balance by Berg balance scale and an intervention program with six games on the Wii Balance Board platform. To statistically analyze the effects before and after intervention were used Wilcoxon test and Pearson correlation with a significance level of p = 0.05. In the present study, we observed a statistically significant improvement in the balance of elderly compared before and after intervention, in addition, the six games played also showed statistical significance when compared to the first and twentieth session, highlighting the following games: Tightrope Walk table Tilt, Deep Breathing and Soccer Heading. Evaluation and balance training with the platform Wii Balance Board were able to provide significant results for the elderly, besides, the game has the potential to address health, wellness and functional capacity of older people through the visual representation of the game in real time